Sphingolipidomics in Translational Sepsis Research–Biomedical Considerations and Perspectives - Claus, Ralf A.; Graeler, Markus H. (Frontiers in Medicine, 2021)
Scientific background: Sphingolipids are a highly diverse group of lipids with respect to physico-chemical properties controlling either structure, distribution or function, all of them regulating cellular response in health and disease. Mass spectrometry, on the other hand, is an analytical technique characterizing ionized molecules or fragments thereof by mass-to-charge ratios, which has been prosperingly developed for rapid and reliable qualitative and quantitative identification of lipid specimens. Parallel to best performance of in-depth chromatographical separation of lipid classes, preconditions of precise quantitation of unique molecular species by preprocessing of biological samples have to be fulfilled. As a consequence, ‘lipid profiles’ across model systems and human specimens, esp. complex (clinical) samples has become eminent over the last couple of years due to sensitivity, specificity and discriminatory capability. Therefore it is significant to consider the entire experimental strategy from sample collection and preparation, data acquisition, analysis and interpretation. Areas covered: In this review we outline considerations with clinical (i.e. human) samples with special emphasis on sample handling, specific physico-chemical properties, target measurements and resulting profiling of sphingolipids in biomedicine and translational research to maximize sensitivity and specificity as well as to provide robust and reproducible results. A brief commentary is also provided regarding new insights of ‘clinical sphingolipidomics’ in translational sepsis research. Expert opinion: The role of mass spectrometry of sphingolipids and related specimens (‘sphingolipidomics’) to investigate cellular and compartment-specific response to stress, e.g. in generalized infection and sepsis, is on the rise and the ability to integrate multiple datasets from diverse classes of biomolecules by mass spectrometry measurements and metabolomics will be crucial to foster our understanding of human health as well as response to disease and treatment.